SOME OBSERVATIONS ON 'STRUCTURE OF ACCOUNTING THEORY' - Chambers, R. J.; Lorig, Arthur N. (The Accounting Review, 1956)
It is relatively short time since university and college courses in accounting began to include theoretical and controversial aspects of the subject in their curricula. Many such institutions still provide only the briefest of introductions to matters of this nature, and very few questions on marginal issues are to be found in the professional examination papers. Where the attempt has been made to extend courses of study beyond the traditional technical boundaries the need must have been felt for a text which deals adequately with the assumptions and concepts of accounting. In the second place, accounting on a cash basis receives only the briefest notice. Yet entities which keep accounts in this way are by no means insignificant. On the one hand are administrative governmental departments and agencies, the transactions of many of these exceed the transactions of most business corporations. On the other hand are large numbers of small business firms, possibly the majority in number of all business units.